Reimagined and redesigned: Recommendations for gender-neutral washrooms and changerooms on campus - Harwood-Jones, Markus; Airton, Lee; Martin, Kel (Canadian Journal of Higher Education, 2023)
Gendered washrooms and changerooms are sites of tension for many transgender and/or gender non-conforming users. However, these are not the only groups impacted by the exclusive provision of gendered spaces. As gender-neutral facilities become increasingly standardized across multiple sectors, we consider how the rising trend of universal design can be realistically adapted withinpost-secondary institutions. This article proposes the concept of inclusive design and provides specific recommendations to improve user experience in gendered and gender-neutral facilities alike on campus.